DIFFICULTIES OF ANTIDRUG-ADDICTION POLICY IN THE YOUTH ENVIRONMENT AND THE ROLE OF EDUCATIONAL INSTITUTIONS IN THIS PROBLEM - T. V. Yakovleva; A. A. Ivanova ("Paediatrician" Publishers LLC, 2012)
Aim. The analysis of a current drug-addiction situation in the Russian Federation and revealing the main causes influencing on drugsdistribution in youth. A substantiation of primary prophylaxis measures against drug-addiction in the education system. Methods. The content-analysis of the drug-addiction situation in modern Russia using various sources of information (the official statistics data, articles, decrees, reports); data received from questionnaires answered by the principals of 124 comprehensive and 65 high schools from various regions of Russia, who have represented themselves as the experts. Results. The main causes of drugs distribution in youth are specificity of age and what is more important, insufficient efficacy of the state anti-drug addiction policy. Conclusions. Implementation and severe control of the realization of the measures against illegal turn and use of drugs both at federal and regional level taking into account territorial special features are required. The necessity of the concept development of the formation of health environment, including anti-drug addiction environment, in educational institutions is also proved.